When prevention fails... A problem not only bedsores hospital - Stafiej, Joanna M.; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Pressure ulcer is considered a chronic wound and is found in patients requiring long-term bed care. It can develop in just a few hours, the treatment is not always successful and the accompanying infection increases the risk of death. Aim : Presenting a case of complete recovery from a grade V decubitus wound in home treatment despite bad prognosis and with employing conservative care. Grade V decubitus wound in a patient at high risk of developing bedsores (9 points in Braden scale and 10 points in Norton scale) treated conservatively with use of new generation dressing. Wound healed completely after 6 weeks. Application of new generation dressing and implants allows for faster and more successful treatment of decubitus wounds.